Transmural Remission Improves Clinical Outcomes Up to 5 years in Crohn's Disease - Raimundo Fernandes, S (2023)
Introduction: Evidence supporting transmural remission (TR) as a long-term treatment target in Crohn's disease (CD) is still unavailable. Less stringent but more reachable targets such as isolated endoscopic (IER) or radiologic remission (IRR) may also be acceptable options in the long-term. Methods: Multicenter retrospective study including 404 CD patients evaluated by magnetic resonance enterography and colonoscopy. Five-year rates of hospitalization, surgery, use of steroids, and treatment escalation were compared between patients with TR, IER, IRR, and no remission (NR). Results: 20.8% of CD patients presented TR, 23.3% IER, 13.6% IRR and 42.3% NR. TR was associated with lower risk of hospitalization (odds-ratio [OR] 0.244 [0.111-0.538], p < 0.001), surgery (OR 0.132 [0.030-0.585], p = 0.008), steroid use (OR 0.283 [0.159-0.505], p < 0.001), and treatment escalation (OR 0.088 [0.044-0.176], p < 0.001) compared to no NR. IRR resulted in lower risk of hospitalization (OR 0.333 [0.143-0.777], p = 0.011) and treatment escalation (OR 0.260 [0.125-0.540], p < 0.001), while IER reduced the risk of steroid use (OR 0.442 [0.262-0.745], p = 0.002) and treatment escalation (OR 0.490 [0.259-0.925], p = 0.028) compared to NR. Conclusions: TR improved clinical outcomes over 5 years of follow-up in CD patients. Distinct but significant benefits were seen with IER and IRR. This suggests that both endoscopic and radiologic remission should be part of the treatment targets of CD.